ETR300 Fundamentals of Entrepreneurship. Business Plan : Green Botanical Garden / Nor Azmina Binti Annuar... [et.al] - Annuar, Nor Azmina; Ismail, Norkhadila; Mahrin, Malawati; Ismail, Mohd Fazirul; Saidi, Haldifi (2010)
After doing extensive research on the business opportunity available in plantation industries, our group has come up with the business plan of partnership whereby our organization’s name will be known as green botanical garden. The General Manager is the head of the business company. This position is responsible for all management for the company that includes employee’s welfare. The entire decision making is in her hand after discussion with the shareholders. She also leading, controlling, planning and looking for the business opportunities. She will assist by other four shareholders that have been agree to cooperated with him to establish the green botanical garden. The first member of this company is Administration Manager. This position will responsible for entire job related to office administration. He will responsible and manage the entire thing that related with his position such as the organizational structure of the company. The second member of this company is Operational Manager. The operational manager will controlled and monitor the operation. He also will manage the business that we organize. In another word, he has the power or an authority to handle all the related work in our company such as making a plan for business location. The third member is Marketing Manager. The function of this position is to prepare the marketing plan or strategy of our business. This person who holds this position must have capability and confident to speak in front of the customer. This is to influence and to attract the customer with our business. The other function is to identifying target share and to develop market strategies. The fourth member of this company is Financial Manager. She will responsible for financial matter and preparing budget financial statement for department expenses. She will manage all the financial company. All the expenditure that will or already use will be monitored and control by her. All the members will be considering as a shareholders that contribute a capital to open this nursery business.